40Ar/39Ar, AFT and (U-Th)/He thermochronologic implications for the low-temperature geological evolution in SE Sweden - Söderlund, Pia (Department of Geology, Lund University, 2008)
The Oskarshamn and Forsmark areas in the Fennoscandian Shield, SE Sweden, have been chosen as potential sites for hosting highly radioactive nuclear waste. To evaluate their respective suitability, the geological history of the bedrock in these two areas has been investigated. This study has focused on the thermal evolution, from c. 500 °C to c. 50 °C. 40Ar-39Ar geochronology on hornblende, muscovite and biotite, was applied to determine cooling from c. 500 °C to c. 300 °C, whereas apatite fission-track (AFT) and (U-Th)/He thermochronology were used to determine the thermal evolution between c. 120 °C and c. 50 °C. The crystalline bedrock in the Forsmark area consists of c. 1.89-1.85 Ga meta-igneous rocks that form part of the Svecofennian orogen. 40Ar-39Ar muscovite ages indicate cooling through c. 350 °C between 1.76 and 1.71 Ga. Biotite ages from surface samples suggest that the present erosion surface cooled below c. 300 °C at 1.73-1.66 Ga. The results show that the area has remained at temperatures below 300 °C since c. 1.7 Ga. The cooling of the Forsmark area reflects either slow cooling after the tectonothermal activity during the Svecofennian orogeny, or uplift in response to far-field effects of 1.7 Ga orogenic activity further to the west (or a combination of these processes). The 1.80 Ga rocks at Oskarshamn belong to the Transscandinavian Igneous Belt (TIB). Younger, 1.45 Ga granites and c. 0.95 Ga dolerite dykes are also present in the area. 40Ar-39Ar hornblende ages indicate initial rapid cooling down to c. 500 °C after the emplacement of TIB rocks. Subsequent cooling through c. 300 °C initially occurred at 1.6 Ga (40Ar-39Ar biotite ages). A 1.51-1-47 Ga 40Ar-39Ar biotite age group reflects either incomplete resetting by younger granitic intrusions in the area or thermal activity related to either the youngest manifestations of rapakivi intrusions or to the initiation of the Danopolonian event in the south. A 1.43-1.42 Ga biotite age group represents cooling after intrusion of the c. 1.45 Ga ...